2010
DOI: 10.5713/ajas.2010.10085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Organic Acids to Substitute Antibiotic Growth Promoters on Performance and Intestinal Microflora of Broilers

Abstract: A grower broiler experiment (from 14 to 35 days of age) was conducted to study the effect of using two commercial mixtures of organic acids (Galliacid ® and Biacid ® ) to substitute antibiotic growth promoter (Eneramycin ® ) on performance, carcass characteristics and intestinal microflora. 400 (Ross 308) broiler chicks were used. A basal corn-soybean meal diet were formulated and served as a control treatment. The control diet was supplemented with either 0.06% Galliacid, 0.1% Biacid or 0.02% Eneramycin. Bird… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
89
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 32 publications
11
89
0
3
Order By: Relevance
“…Regarding the effect of organic acids, the obtained results agreed with previous studies demonstrated that supplementation of organic acids to broiler diets could be used to increased growth performance, reduced diseases and overcome some management problems (Gunal et al, 2006;Islam et al, 2008;Ao et al, 2009;Hassan et al, 2010;Sayrafi et al, 2011;Mohamed et al, 2014). Gunal et al (2006), Islam et al (2008) and Ao et al (2009) concluded that organic acids could be used in poultry as a growth promoter and as a meaningful tool of controlling intrinsic pathogenic bacteria.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Regarding the effect of organic acids, the obtained results agreed with previous studies demonstrated that supplementation of organic acids to broiler diets could be used to increased growth performance, reduced diseases and overcome some management problems (Gunal et al, 2006;Islam et al, 2008;Ao et al, 2009;Hassan et al, 2010;Sayrafi et al, 2011;Mohamed et al, 2014). Gunal et al (2006), Islam et al (2008) and Ao et al (2009) concluded that organic acids could be used in poultry as a growth promoter and as a meaningful tool of controlling intrinsic pathogenic bacteria.…”
Section: Discussionsupporting
confidence: 81%
“…Cengiz et al (2012) reported that supplementation of organic acids to poultry diets was shown to increases beneficial microbial activity in the small intestine. It also suppresses the growth of certain species of bacteria such as Salmonella, E. coli, Clostridium perfringes, Listeria monocytogenes and Campylobacter (Van Immerseel et al, 2002;Hassan et al, 2010;Mohamed et al, 2014). Mohamed et al (2014) found that dietary inclusion of organic acids in broiler diets increased growth performance and improved intestinal morphology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also produces acidic condition that makes the nutrients more available for better performance (Boling et al, 2001). Similarly, our result are also in line with Hassan et al (2010) who stated that organic acids significantly (p<0.001) improved feed conversion ratio. These results also agreed with the findings of Isabel and Santos (2009);Parker (2011), who investigated that organic acid has significantly affected the FCR.…”
Section: Feed Conversion Ratio (Fcr)supporting
confidence: 82%